Disposition of ceftizoxime in Staphylococcal mastitis in Indian crossbred cows. (March 2019) - Buragohain, Rinku; Sar, Tapas Kumar; Samanta, Indranil; Biswas, Ujjwal; Mandal, Tapan Kumar
Highlights: Staphylococci were isolated from six mastitic cows. Ceftizoxime was administered at 20 mg/kg IV as a single dose. Ceftizoxime maintained therapeutic concentration for 120 h post-dose in milk. Bacterial colony count was nil at 96 h post-dose. Abstract: Disposition of ceftizoxime was studied in Indian crossbred cows following a single IV dosing in field conditions. Six healthy lactating and six mastitic crossbred cows were assigned to two groups (Group 1 and Group 2). A single IV administration of ceftizoxime at the dose rate of 20 mg/kg was administered to cows in both groups. Peak concentrations were recorded at 5 min, decreasing sharply until 1 h with plasma concentrations of 46.38 ± 0.30 μg/mL; concentrations were below detection limits at 24 h. Ceftizoxime achieved peak concentrations at 96 h and persisted up to 120 h at a concentration of 36.71 ± 0.96 μg/mL in the milk of mastitic Indian crossbred cows. Staphylococcal colony count in acute mastitis was 52.33 ± 4.98 × 10 5 colony forming units/mL milk and no growth was detected at 96 h post-dosing, indicating that ceftizoxime following single IV administration at 20 mg/kg may be effective to treat acute staphylococcal mastitis.